JAPAN AND THE VALUES OF INCLUSIVE SUSTAINABILITY - Agung Pangeran Bungsu; Fajar Al Mahmudi (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Japan and the values of inclusivity are inseparable. This article briefly describes the revolution of one of the developed countries. Japan is a prime example of a country that has used education to advance and prosper. This country has shown that sincerity and skill in overseeing the education system can change the situation of a country. Character education is a major component of the education system. Good character education will create a progressive, high-quality, and well-characterized society. A developed country can be easily built after society finds its quality. Independence is the milestone of human resource progress to give birth to breakthroughs in the latest innovations. Politeness is the spirit to continue to grow and continue the spirit of struggle. Exemplary behavior in appreciating differences to prioritizing tolerance as evidence of openness to progress. A high work ethic to finally loving tradition is used as capital to continue to contribute to advancing the country. The values of inclusivity reflected in Japan are by continuing to maintain the values of character education